APPROACHES TO HISTORICAL PERIODIZATION OF FINANCIAL CONTROL - Andrey Yu. Volkov; Michael A. Volkov (Статистика и экономика)
Article contains several modes of interpretation the of“ﬁnancial control” term. Concluded: ﬁ nancial control is omnipresent and indispensable way of managing - not only the ﬁnancial system, but also the economyand the hole state generally. At that, state remains the main subject of managing. Moreover, positive qualitative evolutional changes of the ﬁnance control systemcannot be realized without retrospective analysis. Itreveals the main features of ﬁnancial control systemat different stages of formation and development inRussia. Then different modes of periodization of ﬁnance control are explored.